[11C]arachidonic acid incorporation measurement in human brain: Optimization for clinical use. Issue 2 (27th November 2017) - Zanderigo, Francesca; Kang, Yeona; Kumar, Dileep; Nikolopoulou, Anastasia; Mozley, P. David; Kothari, Paresh J.; He, Bin; Schlyer, David; Rapoport, Stanley I.; Oquendo, Maria A.; Vallabhajosula, Shankar; Mann, J. John; et al.
Abstract: Arachidonic acid (AA) is involved in signal transduction, neuroinflammation, and production of eicosanoid metabolites. The AA brain incorporation coefficient (K*) is quantifiable in vivo using [ 11 C]AA positron emission tomography, although repeatability remains undetermined. We evaluated K* estimates obtained with population‐based metabolite correction (PBMC) and image‐derived input function (IDIF) in comparison to arterial blood‐based estimates, and compared repeatability. Eleven healthy volunteers underwent a [ 11 C]AA scan; five repeated the scan 6 weeks later, simulating a pre‐ and post‐treatment study design. For all scans, arterial blood was sampled to measure [ 11 C]AA plasma radioactivity. Plasma [ 11 C]AA parent fraction was measured in 5 scans. K* was quantified using both blood data and IDIF, corrected for [ 11 C]AA parent fraction using both PBMC (from published values) and individually measured values (when available). K* repeatability was calculated in the test‐retest subset. K* estimates based on blood and individual metabolites were highly correlated with estimates using PBMC with arterial input function ( r = 0.943) or IDIF ( r = 0.918) in the subset with measured metabolites. In the total dataset, using PBMC, IDIF‐based estimates were moderately correlated with arterial input function‐based estimates ( r = 0.712). PBMC and IDIF‐based K* estimates were ∼6.4% to ∼11.9% higher, on average, than blood‐based estimates. Average K* test‐retest absolute percent difference values obtained using blood data or IDIF, assuming PBMC for both, were between 6.7% and 13.9%, comparable to other radiotracers. Our results support the possibility of simplified [ 11 C]AA data acquisition through eliminating arterial blood sampling and metabolite analysis, while retaining comparable repeatability and validity. Abstract : Repeatability of [ 11 C]arachidonic acid brain incorporation coefficient measurements, obtained in humans in a 6‐week interval between PET scans to simulate a treatment study design, is comparable to that of other radiotracers used in neuroimaging. Simplifying data acquisition through eliminating blood sampling and metabolite analysis, while retaining repeatability, may be possible.